The Role of Price Perception Mediation on the Quality of Tourist Experience and Satisfaction - Echo Perdana Kusumah; Ratih Hurriyati; Hamsani Hamsani (Universitas Muhammadiyah Sidoarjo, 2020)
Tourist experiences can provide an assessment of a destination by tourists. In the context of island destinations, this study aims to explore deeper the quality of tourist experiences, price perceptions, and tourist satisfaction. The quality of the tourist experience consists of various variables, including escapist, pleasure, relaxation and involvement. A total of 157 samples were obtained through online convenience sampling method for tourists who have visited Belitung Island. Respondents are devoted to tourists who are located outside Belitung Island to avoid biased answers from local residents. Structural Equation Model (SEM) was applied in this study. The results show that only the involvement factor in the quality of tourist experience can influence price perception. Perceptions of prices can indirectly mediate the quality of tourist experiences, except for relaxation. Regardless of the fact that visitors consider the price to be outrageous (expensive or unsuitable), they will still create a positive assessment of the destination if they can involve in the decision-making process. In turn they will be satisfied with their experiences.